Marketing urbanistyczny jako przejaw innowacyjności gmin - Polska, Anna (Urban Marketing as a Symptom of Innovativeness of Communities, 2008)
The subject of the article is urban marketing as an innovative instrument of local spatial planning. The improvement of spatial order is the main task of a community. Urban marketing, as a set of actions supporting local competitiveness, has to be subordinated to the rules of spatial order. However, it is not wide-spread in Poland yet. There is a need to improve this instrument and adopt to the process of spatial planning and urban designing. The article indicates the need to implement innovation into methods of planning. It is shown on the example of Krasnobród, a small town with tourist and health-resorts potential. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 164-174